Deciphering the active deformation of the Guayllabamba depression of Ecuador using fluvial morphometric studies - Cadena Yaguana, Fanny Mariela (2022)
Guayllabamba basin is located in the central zone of the Interandean Valley in the north part of the Ecuador. The genesis of the evolution of this basin is still under study due to its high structural complexity. The Guayllabamba Depression, located on the Guayllabamba basin, is limited by two prominent scarps separated by the Pisque river, which divide them into two apparently similar geometric areas. The slope-area analysis is the most common method used to analyze the river profile. The chi analysis repairs the errors produced by the data, and the results are better than the previous study mentioned. To study the Guayllabamba Depression formation cause, we use chi, steepness index, and concavity plots, the terraces, landslides, and scarps mapping. From the results, we observed the significant difference in volume eroded material of the Guayllabamba Depression concerning the Fluvial terraces of the Guayllabamba river. Furthermore, we noted a concave up shape at the beginning of the profile in the Guayllabamba river and a straight line at the rest of the profile, contrary to the Mira River, which presents a concave up shape along the river. Moreover, we observed there is no linearity on the tributaries with the main stem, and the value of the concavity index to the Guayllabamba river is low. Our results infer that the Guayllabamba basin is a transient landscape and was developed by river erosion and not by tectonic conditions.